Marcadores moleculares na identificação de híbridos e introgressão genética em populações de Pseudoplatystoma corruscans e Pseudoplatystoma reticulatim - Prado, Fernanda Dotti do [UNESP] (2014)
Levels of genetic diversity and structure, as well as the investigation of interspecific and introgressive hybridization events in wild populations, are amongst the major analyzes to be considered in conservation projects. Hybridization between native fish species, especially when caused by human actions, has led to increasing rates of non natural crosses between different taxa, which may cause ecological and genetic impacts. The Neotropical catfish species, Pseudoplatystoma reticulatum and Pseudoplatystoma corruscans, have been affected by the induced production of hybrids in aquaculture and by the contact of these hybrids with their populations. In this study, different genetic markers were developed (genes and microsatellites), in order to identify the occurrence of hybridization and introgression in South American rivers and to access the intra and inter populational genetic diversity of these species. EF1 and 18S nuclear gene markers were completely diagnostics in the identification of the species and their hybrids. Through a Roche 454 pyrosequencing, were developed and characterized 16 microsatellite loci for P. reticulatum, which presented 100% of transferability in P. corruscans and high polymorphism for the majority of the loci. Population analysis using these microsatellites revealed high variability for the both species in all rivers from Paraguay and Paraná hydrographic basins. The interpopulational genetic differentiation of these species within the Paraguay basin was low or absent, revealing a high gene flow and the possible existence of a panmitic population, resulting from the migration and reproduction of individuals from closely rivers. However, significant genetic differences were observed between geographically distant rivers and distinct hydrographic basins. In P. reticulatum, genetic differentiation was found between the Cuiabá and Miranda Rivers (Paraguai basin), and between Paraguay and Lower Paraná ...